How treated the mentally ill offenders? Hazard, security measure and Mental Health Reform - Viana, Itana; Souza, Luis Eugenio de (Journal of Health Law, 2013)
Despite the advances in mental health reform in Brazil with the advent of the Law n. 10.216/2001, the benefi ts of progressive deinstitutionalization and treatment in alternative services have not been extended to people with mental illness who have committed criminal behaviors and were sentenced to detention for compulsory treatment in an establishment of the prison system - the Hospitals of Custody and Psychiatric Treatment (HCTP). In this study, we describe the HCTP of the state of Bahia, in the moment of an intervention by the State Public Ministry, and we review the historical evolution of treatment of mentally ill offenders. Thereafter, we discuss the obstacles to the psychiatric reform in the penalty area and the possibilities of overcoming them. Finally, we point out the need to strengthen inclusive health policies and to change laws and judicial practices, which also requires the overcoming of prejudices socially widespread.